Lifestyle profile of elderly living with non-communicable disease in Bangkok and Surabaya - Ni Putu Wulan Purnama Sari; Jintana Artsanthia (International Journal of Public Health Science (IJPHS), 2019)
Lifestyle is one of the underlying risk factor of non-communicable disease (NCD). Dietary habit and exercise pattern are two indicators of lifestyle. Elderly are prone to NCD due to increased age which being independent risk factor. This study aimed to analyze and compare the lifestyle profile of elderly living with NCD between Bangkok and Surabaya, in term of dietary habit and exercise pattern, and to determine the best predictor of sedentary lifestyle among this population. This cross-sectional study involved 100 and 96 elderly with HT and/or DM in communities of Bangkok and Surabaya respectively (n=196). Self-developed instrument was used in data collection (r=0.178–0.715, Chronbach Alpha=0.644). Mann-Whitney U and regression tests were used in data analysis (α<0.05). There was a significant difference of lifestyle in elderly living with NCD between Bangkok and Surabaya (p=0.008), especially in term of eat variety food (p=0.002), oily food (p=0.015), and curry with coconut milk (p=0.026). Eat vegetable and fruit could not predict dietary habit in elderly living with NCD (p=0.064). Eat fermented food was came up as the best predictor of lifestyle (p=0.000). It was accounted for 52.1% variance in lifestyle score in this population.